Occurence of ecto- and endo parasites in pigeon (Columba livia Linn.) - Musa, Sharmin; Afroz, Sharmin Dil; Khanum, Hamida (University Journal of Zoology, Rajshahi University, 2012)
DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10758 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 73-75